Insights into Aqueous Organic Redox Flow Batteries: Key Physicochemical Determinants of Electrochemical Behavior - Joy, Kabir (My University, 2025)
The development of high-performance organic redox flow batteries (ORFBs) is vital to enable cost-effective and sustainable energy storage solutions for renewable energy systems. This thesis focuses on the role of physicochemical properties—solubility, redox potential, and kinetic parameters (electron transfer rate constant k₀ and diffusion coefficient D₀)—in determining the performance of ORFBs operating in alkaline media. Particular attention is given to anolytes, or negative redox-active species, capable of two-electron storage, such as quinones, phenazines, and other organic molecules with tunable redox properties. The use of two-electron storage compounds offers the potential to enhance the charge storage capacity per molecule, yet their design and optimization remain a significant challenge due to limited chemical stability and solubility. This thesis investigates how structural modifications influence the solubility and redox potentials of these compounds and how these changes translate into improved energy density and power density of the battery. Additionally, while k₀ and D₀ are often reported in literature, their individual impact on battery performance is rarely analyzed. Voltametric simulations are conducted to assess the effect of these kinetic parameters on battery reversibility and efficiency. The preliminary findings indicate that variations in D₀ have minimal effect on performance, whereas changes in k₀ significantly influence the reversibility of the redox process. By combining a comprehensive literature review with computational simulations, this thesis aims to identify the most influential physicochemical factors for designing next-generation ORFB anolytes. The results are expected to guide the development of organic molecules with improved electrochemical performance for large-scale, long-duration energy storage.
Keywords: Redox Flow Batteries, Organic Redox Flow Battery (ORFB), Aqueous Organic Redox Flow Battery (AORFB), Electrochemical Kinetics, Electron Transfer Rate Constant (k0), Diffusion Coefficient (D₀), Multi-Electron Transfer, Cyclic Voltammetry (CV), Convective Mass Transport, Molecular Engineering